Heterogeneous outcomes of liver disease after heart transplantation for a failed Fontan procedure. (22nd July 2021) - Ybarra, Aecha M; Khanna, Geetika; Turmelle, Yumirle P; Stoll, Janis; Castleberry, Chesney D; Scheel, Janet; Ballweg, Jean A; Ameduri, Rebecca; Kimberling, Matthew; Makil, Elizabeth; Birnbaum, Brian F; Exil, Vernat; et al.
Abstract: Background: Fontan‐associated liver disease (FALD) uniformly affects patients with long‐term Fontan physiology. The effect of isolated heart transplant (HT) on the course of FALD post‐HT is not well understood. Methods: We evaluated serial liver imaging pre‐ and post‐HT to assess liver changes over time in a single‐center retrospective analysis of Fontan HT recipients who had pre‐ and ≥1‐year post‐HT liver imaging. Available patient demographic and clinical data were reviewed, including available liver biopsy results. Results: Serial liver imaging was available in 19 patients with a median age at HT of 12 years (range 3–23), the median age from Fontan to HT of 5.7 years (range 0.8–16), and the median time from imaging to follow up of 27 months (range 12–136 months). Pre‐HT liver imaging was classified as follows: normal (n=1), congested (n=9), fibrotic (n=7), and cirrhotic (n=2). The majority of transplanted patients (15/19) had improvement in their post‐HT liver imaging, including 13 patients with initially abnormal imaging pre‐HT having normal liver imaging at follow‐up. One patient had persistent cirrhosis at 26‐month follow‐up, one patient had unchanged fibrosis at 18‐month follow‐up, and one patient progressed from fibrosis pre‐HT to cirrhosis post‐HT at 136 months. No patients had overt isolated liver failure during pre‐ or post‐HT follow‐up. Liver biopsy did not consistently correlate with imaging findings. Conclusions: Post‐HT liver imaging evaluation in Fontan patients reveals heterogeneous liver outcomes. These results not only provide evidence for the improvement of FALD post‐HT but also show the need for serial liver imaging follow‐up post‐HT.